Optimal Composition and Study of The Physical and Mechanical Properties of High-Strength Heavy Concrete - o’g’li, Botirov Bektosh Farhod; B., Berdiyev O. (European Journal of Life Safety and Stability (2660-9630), 2022)
In this research the authors research optimal composition and study of the physical and mechanical properties of high-strength heavy concrete and improve the quality of concrete constructions. High-strength heavy concrete that have a water/binder ratio between 0.30 and 0.40 are usually more durable than ordinary concrete not only because their capillarity and pore networks. So, the concrete sample specimens were tested for physical and mechanical properties which are related to durability. And each consist has 300 kg/m3. After 28 days compressive strength increases to 40MPa and after 90 days 61MPa were achieved. Also tested flexural properties after 28 days got 4.7 and after 90 days 5.7MPa.